SAT0227 An academic arthritis website is most frequently utilised for arthritis news and treatment information. (1st June 2001) - White, JM; Bathon, JM; Matsumoto, AK
Abstract : Background: Medical and pseudo-medical information sites are the most heavily trafficked sites on the Worldwide Web. The Hopkins Arthritis Web Site was launched in late December 1998 to provide credible information about arthritis and its treatment to health care providers and patients. Objectives: Our goal was to evaluate the topics most frequently accessed by visitors to the Site. Methods: The information data base on the Site consists of a large body of ?static? information, as well as two interactive forums. The number of ?requests? for each page was monitored by Web Trends Enterprise Reporting Server. The number of requests per page was adjusted for number of months that the page was live, and sorted by topic into 1 of 6 categories. Requests were readjusted for number of pages per topic and calculated as a percent of total requests. Data were based on statistics compiled for the year 2000. Results: The frequency of visits to the ?static? pages were as follows: news items (27%), pharmacologic treatment (21%), diagnostic/therapeutic guidelines (21%), event broadcasts (12%), disease-specific education (10%), and nonpharmacologic management (8%). Highlights of the ACR meetings were one of the most heavily accessed ?news item? postings on the Site. For the interactive forums, treatment related postings constituted the majority of postings: 55% of questions in ?Ask the Expert?, and 70% of postings to the Message Board. ?Hits? to the Site, and time spent on the Site, have increased steadily since launch, currently totalling 1, 200, 000 hits and 12 min per month, respectively. Conclusion: The versatility of the Internet confers the unique ability to constantly update educational data bases. The desire for updated information is reflected on this Arthritis Web Site by the high frequency of visits to treatment and news related pages. Credible educational websites can effectively complement traditional on-site educational forums.